2019
DOI: 10.1111/jne.12697
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia‐induced seizures followed by repetitive stress are associated with age‐dependent changes in specific aspects of the mouse stress system

Abstract: Stress is among the most frequently self-reported factors provoking epileptic seizures in children and adults. It is still unclear, however, why some people display stress-sensitive seizures and others do not. Recently, we showed that young epilepsy patients with stress-sensitive seizures exhibit a dysregulated hypothalamic-pituitaryadrenal (HPA)-axis. Most likely, this dysregulation gradually develops, and is triggered by stressors occurring early in life (early-life stress [ELS]). ELS may be particularly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Deciphering the interaction of different immune cytokines with neuronal circuits of stress is critical to delineate the physiological and psychological stress responses and the prognosis of illness (Godoy et al, 2018). It is proved, experimentally, that hyperthermia and early life stresses in the murine model resulted in deregulation of hypothalamic-pituitary-adrenal (HPA) axis, skewing of hippocampal glucocorticoid receptor mRNA expression and defective neurogenesis indicated by the immature neuron marker doublecortin in an age-dependent manner (Umeoka et al, 2019). Advances in proteomic research have come up with various potential proteins as a panel of biomarkers for diagnosis and therapy related to immunity, blood coagulation, management of oxidative stress, energy metabolism, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Deciphering the interaction of different immune cytokines with neuronal circuits of stress is critical to delineate the physiological and psychological stress responses and the prognosis of illness (Godoy et al, 2018). It is proved, experimentally, that hyperthermia and early life stresses in the murine model resulted in deregulation of hypothalamic-pituitary-adrenal (HPA) axis, skewing of hippocampal glucocorticoid receptor mRNA expression and defective neurogenesis indicated by the immature neuron marker doublecortin in an age-dependent manner (Umeoka et al, 2019). Advances in proteomic research have come up with various potential proteins as a panel of biomarkers for diagnosis and therapy related to immunity, blood coagulation, management of oxidative stress, energy metabolism, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Such animal studies have shown that hyperthermia-induced seizures occurring early in life may dysregulate central components in an agedependent manner, conferring higher vulnerability of this cohort to develop epilepsy. 18 Based on the current literature, an imbalance between proinflammatory and anti-inflammatory cytokines might play a role in the pathogenesis of febrile seizures. Sahin et al reviewed the effect of interleukin 12 (IL-12) a proinflammatory cytokine, IL-10 an anti-inflammatory cytokine, and interferon B and demonstrated reduced cerebrospinal fluid levels of IL-10 in febrile seizure patients in response to inflammatory conditions.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…In addition to receptors and ion channels, dysregulation of glial functions, such as malfunction and/or downregulation of glutamate transporters, is involved in the generation of epileptic seizures and pathological changes of MTLE [ 22 , 23 ]. Both experimental and clinical investigations suggest that several factors, such as the frequency [ 24 ] and intensity [ 25 ] of seizures, prolonged seizures [ 26 ], anticonvulsants [ 27 , 28 ], age of onset [ 29 , 30 ], and psychiatric/cognitive abnormalities [ 31 ], could affect the histological and molecular architecture of the epileptic brain. The expression levels of various genes of both the human epileptic hippocampus and amygdala were investigated.…”
Section: Introductionmentioning
confidence: 99%